2020
DOI: 10.1007/s11657-020-00790-9
|View full text |Cite
|
Sign up to set email alerts
|

Response regarding the importance of vitamin D and calcium among undergraduate health sciences students in Al Kharj, Saudi Arabia

Abstract: Background Vitamin D and calcium are essential dietary components for human body, and their deficiency is linked to poor bone health and osteoporosis. Adequate knowledge of health staff regarding vitamin D and calcium is critical for general population awareness. The current work was to evaluate the awareness regarding the importance of vitamin D and calcium among undergraduate health science students in Al Kharj. Methods A self-distributed validated questionnaire-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The mean of knowledge score of the participants in this study was 31.3%, which is close to previously reported scores in China (20) and Canada(21) but signi cantly lower than that of undergraduate health science students in Saudi Arabia (22).…”
Section: Knowledge Scoresupporting
confidence: 85%
“…The mean of knowledge score of the participants in this study was 31.3%, which is close to previously reported scores in China (20) and Canada(21) but signi cantly lower than that of undergraduate health science students in Saudi Arabia (22).…”
Section: Knowledge Scoresupporting
confidence: 85%
“…In fact, the proportion of those with a good knowledge of vitamin D (45%) among health educators in public schools is considered insufficient in terms of how important it is to communicate such knowledge to students and teachers. However, other studies among different populations, including the general population and university students within Saudi Arabia have reported inconsistent findings [ 23 , 30 , 31 ]. For example, a study that examined the knowledge of vitamin D among the general population in Jeddah, Saudi Arabia, reported the overall knowledge at approximately 39% [ 23 ], which is lower than the rate reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted among the general population in Al-Baha city, Saudi Arabia, reported that 69.5% of study participants had adequate knowledge of vitamin D [ 30 ]. Similarly, a study conducted among university students in Al-Kharj city, Saudi Arabia, reported that 85% of study participants had a good knowledge of vitamin D [ 31 ]. However, no previous studies have examined the knowledge of and attitude towards vitamin D among health educators in schools in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study carried out in Saudi Arabia showed that women exhibit a lower general exposure to the sun, although their knowledge about vitamin D importance is greater than in men (P < 0•002) (58) . Moreover, they take vitamin D supplements more frequently than men (59) . Furthermore, baseline characteristics of participants in the Vitamin D and OmegA-3 TriaL (VITAL) in the USA suggest more frequent consumption of foods containing vitamin D by women than men (60) .…”
Section: Sex Differences In the Serum Levels Of Vitamin Dmentioning
confidence: 99%